The American criminal justice system: how it works, how it doesn't and how to fix it - Falk, Gerhard (Praeger)
The American police -- A brief history of criminal prosecution in America -- Prosecuting violent crime and sex offenses -- Prosecuting "white collar" crime -- Defending the accused -- The American jury -- Courts and judges -- The prison-industrial complex -- Probation and parole -- The death penalty : non omnis moriar